A work study on Noritake Porcelana Mfg., Inc. - Coeli, Clare T. (College of Engineering, 1997)
The company under study is Noritake Porcelana Mfg. Inc. which is the manufacturing arm of Noritake Limited-Japan. The group documented the system through observations, interviews and data gathering. It was found out that the main problem of the company is the high occurence of overtime. The group traced the causes and generated possible solutions to decrease overtime. This study provided the company with guidelines and time standards to be able to implement the proposed alternatives.